Systemic climate litigation: a complex type of structural process - Glave Mavila, Carlos (2025)
The paper takes the existence of national lawsuits discussing climate liabilities as an example to highlight the adaptation of procedural law in relation to the design of collective actions and, more specifically, structural litigation. The author holds that systemic climate litigation lawsuits are an example of a very complex structural process that is impossible, illogical, and incoherent to be handled under the standards of a procedure designed for the protection of individual rights, such as it is in Perú. Because it is very likely that an increasing number of lawsuits in which climate liabilities are claimed will arise, the paper seeks to open the discussion in Peru on the design of a procedure addressing structural controversies; as well as to begin to discuss whether, and to what extent, it is possible for national courts, under a proper design of structural procedure, to handle disputes in which climate liabilities are claimed.